Community, complexity, the public library and community orientation. Issue 6 (26th August 2014) - Sen, Barbara
Abstract : Purpose: – The purpose of this paper is to present a model of the complexity in public libraries based on a case study of Cumbria Libraries, a public library service in the North West of England. The model illustrates the complexity of the library as a societal organisation with multiple stakeholder perspectives. The model is based on community orientation as a form of market orientation, in combination with other multiple strategic orientations that combine to add value for stakeholders within the community. Design/methodology/approach: – The study is based on a case study of Cumbria Libraries. The data were gathered during field visits via conversations, interviews, photographs, documents and observations and includes 85 participants from multiple stakeholder groups. The analytical approach blended thematic and situational analyses. Findings: – A key finding was the existence of multiple strategic orientations, the criticality of the leadership roles in managing the complexity and in motivating staff and community stakeholders towards offering a cohesive and relevant service suitable for community needs. Originality/value: – There is currently no literature on strategic orientation in libraries. The paper present an original model illustrating the complexity of the strategic orientations identified within the case study.